Calcium and contribution to the normal development of bones: evaluation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006. (20th October 2016) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following an application from Specialised Nutrition Europe (formerly IDACE), submitted for authorisation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006 via the Competent Authority of France, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to calcium and contribution to the normal development of bones. The Panel considers that calcium is sufficiently characterised and that contribution to the normal development of bones is a beneficial physiological effect. The target population proposed by the applicant is infants (from birth) and young children up to 3 years of age. The Panel has previously assessed a claim on calcium and normal growth and development of bone with a favourable outcome. The target population was children and adolescents. The Panel considers that the role of calcium in the development of bones applies to all ages including infants and young children up to 3 years of age. The Panel concludes that a cause and effect relationship has been established between the dietary intake of calcium and contribution to the normal development of bones.